Implementation of building permit policy after natural disaster Palu city in 2018 - Ince Dian Afnita; Muhammad Nur Ali; Sitti Chaeriah Ahsan (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study aims to analyze the obstacles to the implementation of the post-disaster Building Construction Permit (IMB) policy in Palu City, based on Regional Regulation No. 9 of 2022. The primary focus of this study is to analyze the extent to which the policy aligns with the post-disaster socio-economic and geographical context, and to identify factors that hinder its effective implementation. This study employed a descriptive qualitative method, with data collection techniques including in-depth interviews, participant observation, focus group discussions (FGDs), and documentation studies. Information was collected from 12 informants from government agencies, affected communities, and local stakeholders. The results indicate that policy implementation has not been optimal due to six main factors: a lack of understanding of the policy's objectives and standards, limited human resources and infrastructure, overlapping authority between agencies, unintegrated communication, limited authority and training for implementers, and socio-economic conditions that do not support regulatory compliance. These findings indicate a gap between national policy and local realities in disaster-affected areas. This research provides an empirical contribution to the study of public policy implementation in the disaster context and offers contextual and inclusive policy recommendations. The practical implications of this research include the need to simplify licensing procedures, strengthen inter-agency coordination, and adjust regulations to local post-disaster conditions.